A Dynamic Theory of Network Failure: The Case of the Venice Film Festival and the Local Hospitality System. Issue 5 (May 2016) - Moretti, Anna; Zirpoli, Francesco
Organizational and sociological research dealing with network governance has mainly focused on network advantages rather than on their problems or dysfunctionalities. This focus has left the field of network failure partially unexplored. We argue that although there have been some attempts to explicitly theorize network failures, the existing explanations, which are based on structural or social conditions, are not exhaustive. In this article we report the results of our empirical investigation on an underperforming network formed by the world-famous Venice Film Festival and its local hospitality system. We inductively derive a dynamic theory of network failure premised on the interplay of the network's static dimensions (opportunism and ignorance) and dynamic dimensions (framing and mobilizing), and the role of institutions.